2016
DOI: 10.1074/jbc.m116.735126
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen and Ultraviolet A Light Treatment Directly Affects Phosphatidylinositol 3-Kinase Signal Transduction by Altering Plasma Membrane Packing

Abstract: Edited by George CarmanPsoralen and ultraviolet A light (PUVA) are used to kill pathogens in blood products and as a treatment of aberrant cell proliferation in dermatitis, cutaneous T-cell lymphoma, and graftversus-host disease. DNA damage is well described, but the direct effects of PUVA on cell signal transduction are poorly understood. Because platelets are anucleate and contain archetypal signal transduction machinery, they are ideally suited to address this. Lipidomics on platelet membrane extracts showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Experimental research has demonstrated that quality control parameters of Intercept pathogen‐inactivated platelets generally are within predefined ranges but with a significant impact on in vitro function . This is caused by irreversible changes in the platelet plasma membrane which affect subsequent intracellular signal transduction . Clinical studies have demonstrated significantly lower corrected count increments at 1 and 24 h, shorter transfusion intervals and increased transfusions of Intercept‐treated platelets compared to standard concentrates .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research has demonstrated that quality control parameters of Intercept pathogen‐inactivated platelets generally are within predefined ranges but with a significant impact on in vitro function . This is caused by irreversible changes in the platelet plasma membrane which affect subsequent intracellular signal transduction . Clinical studies have demonstrated significantly lower corrected count increments at 1 and 24 h, shorter transfusion intervals and increased transfusions of Intercept‐treated platelets compared to standard concentrates .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments on circulating lymphocytes demonstrated that apoptotic process is observable from 12 h after irradiation, increasing at 24 and 48 h and being directly proportional to UVA and 8‐MOP doses . Moreover, some recent findings have identified a systemic effect on inflammation by the modulation of pro‐inflammatory cytokines and the inhibition of the signal transduction in the phosphatidylinositol 3‐kinase (PI3K) pathway …”
Section: Puva: Mechanisms Of Action and Uses In Mf/ssmentioning
confidence: 99%
“…35,36 Moreover, some recent findings have identified a systemic effect on inflammation by the modulation of pro-inflammatory cytokines 37 and the inhibition of the signal transduction in the phosphatidylinositol 3-kinase (PI3K) pathway. 38 The theoretical advantages of PUVA over NB-UVB are in terms of reduced erythemogenic activity and better penetration towards deeper dermal layers, up to hypoderma and deepest adnexal structures. 11 This has been empirically confirmed by studies comparing efficacy among PUVA and NB-UVB in patients with MF.…”
Section: Nb-uvb In Mf/ssmentioning
confidence: 99%
“…24 In regard to pathogen reduction technology implementation which seeks to make the platelet inventory safer for recipients, it should be of interest that use of psoralen and ultraviolet A light therapy on platelets inhibits signal transduction and normal docking of liposomes onto α-synuclein. 25 These findings suggest that looking at α-synuclein concentration increases as a surrogate biomarker of changes to platelet biology in response to such technology may prove essential to determine if use of pathogen reduction leads to changes in platelets' health. Similarly, in light of the current increased interest in using cold-stored platelets, [26][27][28] it would also be of interest to establish whether α-synuclein concentration changes can also be indicative of platelet health in this setting as well.…”
Section: α-Synuclein Is Also Known To Be Immunogenic As In Patients Withmentioning
confidence: 99%